2019
DOI: 10.1186/s12888-018-2006-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between subclinical hypothyroidism and depression: an updated systematic review and meta-analysis

Abstract: BackgroundAlthough depression is associated with changes in the hypothalamic-pituitary-thyroid axis, its relationship with subclinical hypothyroidism (SCH) is controversial. To date, there is a lack of data on the improvement of depressive symptoms with levothyroxine therapy among individuals with coexistent SCH.MethodsWe conducted a meta-analysis to evaluate the association between SCH and depression including 1) the prevalence of depression in SCH (with a sub-analysis of the geriatric cohort), 2) thyroid sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 50 publications
(88 reference statements)
3
50
2
7
Order By: Relevance
“…However, only a small fraction of children and adolescents in either study was affected by HYPO SC when applying a pediatric reference range for TSH. Drawing on a sample of children and adolescents affected by HYPO SC , Cerbone et al ( 8 ) found no relationship between HYPO SC and mental health, which is supported by results of the present study as well as the two most recent meta-analyses of the relationship between HYPO SC and depression in adults ( 73 , 74 ). Tang et al ( 74 ) showed in a subgroup analysis that only adults aged 50 and above were more likely to experience depression which agrees with considerations by Dayan and Panicker ( 75 ), arguing that an underlying chronic condition, more likely to occur in the elderly, could be the cause of increased rates of depression in adults rather than HYPO SC .…”
Section: Discussionsupporting
confidence: 87%
“…However, only a small fraction of children and adolescents in either study was affected by HYPO SC when applying a pediatric reference range for TSH. Drawing on a sample of children and adolescents affected by HYPO SC , Cerbone et al ( 8 ) found no relationship between HYPO SC and mental health, which is supported by results of the present study as well as the two most recent meta-analyses of the relationship between HYPO SC and depression in adults ( 73 , 74 ). Tang et al ( 74 ) showed in a subgroup analysis that only adults aged 50 and above were more likely to experience depression which agrees with considerations by Dayan and Panicker ( 75 ), arguing that an underlying chronic condition, more likely to occur in the elderly, could be the cause of increased rates of depression in adults rather than HYPO SC .…”
Section: Discussionsupporting
confidence: 87%
“…A study by Guimarães et al [ 40 ] based on almost 1300 Brazilian, middle-aged women from urban areas demonstrated that women with a high TSH level (>10 mUI/mL) had a three-fold higher chance of presenting depressive symptoms than women having with levels of TSH. In contrary, Loh et al [ 41 ] reported no significant difference in the mean TSH level between individuals with depression and healthy controls (2.30 vs. 2.13 mIU/L, respectively).…”
Section: Discussionmentioning
confidence: 95%
“…The low efficacy of pharmacotherapy is probably because the antidepressant drugs currently in use mainly affect noradrenergic and serotonergic neurotransmission, while many studies have shown that this disease involves not only disturbances in neurotransmission but also changes in hormonal systems, immune systems, and energy processes that together impair synaptic plasticity, leading to numerous functional changes, including depressed mood (Horowitz and Zunszain, 2015). The participation of thyroid hormones in the pathogenesis of depression is evidenced by epidemiologic data that indicate that thyroid dysfunction often leads to the development of mental diseases; among patients with affective disorders, 1-4% have hypothyroidism, and 4-40% present subclinical hypothyroidism (Duntas and Maillis, 2013;Loh et al, 2019). The therapeutic effectiveness of adjunctive treatment of refractory depression with superphysiological doses of thyroid hormones is well established, but the mechanism of action of thyroid hormones on the function of the central nervous system in adults is not well known (Bauer et al, 2002(Bauer et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%